ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT WIRAUSAHA MAHASISWA - Sunnatullah, Masbanyu Priyayi; Nawarcono , Winanto; Ekowati, Dhiana (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Entrepreneurship in Indonesia is still completely unable to lift positive contributions from the current poverty line, even though the potential for entrepreneurship is currently very large with various current conditions by issuing their own creative ideas. education. entrepreneurship. The university is responsible for educating and providing entrepreneurial skills to its students so as to create a generation that dares to choose entrepreneurs.This study aims to determine (1) the factors that influence student interest in entrepreneurship (2) determine the motivational factors affect the interest of entrepreneurial students (3) from the motivational factors affect the interest of entrepreneurial students (4) from the family environment influence factors influence the interest entrepreneurial students (5) from business capital factors influencing student entrepreneurial interests (6) from creativity factors influencing entrepreneurial student interests (7) proving that there are factors that influence student interest in entrepreneurship.This researcher uses a qualitative approach with the type of correlational research. This research was taken from 100 students throughout the 2017 – 2021 class as research subjects. The research instrument used a questionnaire, while the collection technique used a questionnaire. And data analysis using multiple regression.The results of this study there is a significant positive influence between all factors on motivation and family environment.